Claims of global warming on major aquatic habitats a clarification using thematic content analysis - Espia, Micah P.
This quantitative research studied the familiarized claims and projected global warming (GW) consqquences on major aquatic habitats (MAH) in the Philippines utilizing articles published online from 1991 through 2015.Specifically, this study aimed at verifying the publicized claims about human-induced GW and then assessing the certainty of their projected consequences on the MAH. Purposive and stratified sampling was used to select 120 articles. The data gathering instrument was a coding form structured with predefined categories and subcategories based on study objectives. The independent variables were background data such as authorship, affiliation, GW belief, reasons for GW belief, collaboration, article theme, audience, references, nature of the article, and publication type. On hte other hand, the dependent variables were the 12 most popular dimensions f GW consequences based on IPCC's report (2013) for climate extremes, namely, CO2 Increase, Changes of Indicator Species, diseases, Flooding, Ocean Acidification, Polar Ice, Rainfall/Droughts, Sea Level Rise, SST Increase, STS and TC, Wind and Wave Increase, and other GW Extremes.Thematic contentanalysis was used to survey the familiarized claims and projected GW consequences on MAH. Results were analyzed using the frequency, mean, standard deviation, analysis of variance (ANOVA) set at .05 level of significance, and multiple linear regression. Overall, this study has shown that there is no validated proof of increase in climatic disasters in the Philippines due to anthropogenic GW (AGW), and that the existing global warming/climate change programs have no scientific basis. In fact, 70% of these studies made use of qualitative review and compilation in assessing AGW consequences on MAH, with 485 basing their projections on IPCC reports. ANOVA revealed that there is no significant way of differentiating the claims of AGW impacts on MAH. Moreover, multi-regression showed that here is no significant way of predicting the AGW consequences based on the study themes.